2021
DOI: 10.3390/ijerph18147398
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions Related to Nursing and Nursing Staff in Long-Term Care Settings during the COVID-19 Pandemic Era: Using Social Networking Service

Abstract: Purpose: The purpose of this study was to investigate what opinions and perceptions people have about nursing and the role of nursing staff in nursing homes (NHs) on Social Networking Service (SNS) by analyzing large-scale data through social big-data analysis. Methods: This study investigated changes in perception related to nursing and nursing staff in NHs during the COVID-19 pandemic era using target channels (blogs, cafes, Instagram, communities, Twitter, etc.). Data were collected on the channel from 12 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…In a study by Rosenberg, Syed, and Rezaie (2020) which evaluated the role of Twitter use during the pandemic, positive attitudes such as the selfsacrifice, dedicated efforts and positive experiences of healthcare professionals in frontline intervention were reported and it was emphasized that the healthcare professionals were seen as heroes (El-Awaisi, O'Carroll, Koraysh, Koummich & Huber, 2020). In a study in Korea which evaluated through social media the public perception of nurses and the nursing profession before and after the pandemic, it was reported that the importance of nurses in preventing and managing a mass epidemic was better understood since the COVID-19 pandemic (Shin, Jung, Park, Lee and Son, 2021). As seen in other research results, a positive attitude developed to nurses and to all healthcare professionals during the pandemic, similar to the results of the current study.…”
Section: Discussionsupporting
confidence: 88%
“…In a study by Rosenberg, Syed, and Rezaie (2020) which evaluated the role of Twitter use during the pandemic, positive attitudes such as the selfsacrifice, dedicated efforts and positive experiences of healthcare professionals in frontline intervention were reported and it was emphasized that the healthcare professionals were seen as heroes (El-Awaisi, O'Carroll, Koraysh, Koummich & Huber, 2020). In a study in Korea which evaluated through social media the public perception of nurses and the nursing profession before and after the pandemic, it was reported that the importance of nurses in preventing and managing a mass epidemic was better understood since the COVID-19 pandemic (Shin, Jung, Park, Lee and Son, 2021). As seen in other research results, a positive attitude developed to nurses and to all healthcare professionals during the pandemic, similar to the results of the current study.…”
Section: Discussionsupporting
confidence: 88%
“…For example, most Spanish patients appreciated the humanised nursing care received during the pandemic in terms of the quality of nursing practice, nurses' willingness to care and their openness to nurse-patient communication [51]. A Korean study demonstrated that as a result of the pandemic, the role of nursing staff in the prevention and management of mass infections has been recognised by the public [52]. Almost 86% of nursing students in China believed that COVID-19 had a beneficial influence on the image of nursing [53].…”
Section: Discussionmentioning
confidence: 99%
“… 13 On the other hand, it helps to provide an in-depth analysis of the nurses’ lived perceptions during the different waves of the pandemic, which might shape the public perceptions of the role of nurses, even after the pandemic. 14 …”
Section: Introductionmentioning
confidence: 99%
“…13 On the other hand, it helps to provide an in-depth analysis of the nurses' lived perceptions during the different waves of the pandemic, which might shape the public perceptions of the role of nurses, even after the pandemic. 14 Several studies have described the nurses' experiences on social media during the first COVID-19 pandemic wave. [15][16][17][18][19] O'Leary et al 15 have considered the online interactions, the social networks, and the perspectives of nurses at the individual and organization levels by examining the conversations about COVID-19 that emerged on Twitter from 10 March 2020 to 10 May 2020.…”
Section: Introductionmentioning
confidence: 99%